2013
DOI: 10.1186/1756-0500-6-436
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted radical prostatectomy: a case series of the first 100 patients -constitutional introduction and implementation on the basis of comprehensive department of minimal invasive surgery center-

Abstract: BackgroundAlthough a very small number of Japanese hospitals had been performing robotic surgery before 2011, the number now using it is increasing rapidly due to the application of health insurance to robotic surgery for prostate cancer (PCa) since April, 2012. We report our initial experience of treating 100 patients by robot-assisted radical prostatectomy (RARP) with a focus on constitutional introduction and implementation based on minimal invasive surgery center (MISC) and patient outcomes.MethodsThe MISC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
3
5
0
1
Order By: Relevance
“…In none of our cases, as in those recently reported by another group evaluating initial RARP experience, was intraoperative open conversion required. 10 Our rate of severe complications (Clavien 3b or more) was 5.8% (9/154) in the entire series of patients and 10.7% (3/28) in the G3 patients, and these rates are similar to the severe complication rates found in previous studies. 9,11 However, two of the three patients with grade 3b complications in G3 showed severe ileus that required open revision.…”
Section: Discussionsupporting
confidence: 89%
“…In none of our cases, as in those recently reported by another group evaluating initial RARP experience, was intraoperative open conversion required. 10 Our rate of severe complications (Clavien 3b or more) was 5.8% (9/154) in the entire series of patients and 10.7% (3/28) in the G3 patients, and these rates are similar to the severe complication rates found in previous studies. 9,11 However, two of the three patients with grade 3b complications in G3 showed severe ileus that required open revision.…”
Section: Discussionsupporting
confidence: 89%
“…PSM rates in pathological 2, 3, and total were 9.3%, 47% and 22%, respectively, which was comparable with the 4–23%, 29–50% and 6.5–32%, respectively, reported in a recent study . In addition, the present oncological outcomes are better than those of a Japanese initial series in which PSM rates in pathological 2, 3, and total were 10–21%, 44–78% and 19–27%, respectively (Table S1). The present study also showed the differential pattern of PSM between a mentor and new surgeons with a mentor.…”
Section: Discussionsupporting
confidence: 85%
“…Our operative technique, involving a transperitoneal approach, was carried out as previously described. 6 In principle, the indicators for RARP are the same as for open prostatectomy, and patients with clinical stage T1c−2c prostate cancer were considered candidates for the procedure. However, several clinical T3 patients underwent RARP because of other factors, such as when their PSA level or the number of positive cores from their prostate biopsies indicated the possibility of organconfined cancer.…”
Section: Methods Patientsmentioning
confidence: 99%